Asymptotic-Preserving Scheme for the M1-Maxwell System in the Quasi-Neutral Regime (Communications in Computational Physics, 2018)
This work deals with the numerical resolution of the M1-Maxwell systemin the quasi-neutral regime. In this regime the stiffness of the stability constraints ofclassical schemes causes huge calculation times. That is why we introduce a new stablenumerical scheme consistent with the transitional and limit models. Such schemesare called Asymptotic-Preserving (AP) schemes in literature. This new scheme is ableto handle the quasi-neutrality limit regime without any restrictions on time and spacesteps. This approach can be easily applied to angular moment models by using a momentsextraction. Finally, two physically relevant numerical test cases are presentedfor the Asymptotic-Preserving scheme in different regimes. The first one correspondsto a regime where electromagnetic effects are predominant. The second one on the contraryshows the efficiency of the Asymptotic-Preserving scheme in the quasi-neutralregime. In the latter case the illustrative simulations are compared with kinetic andhydrodynamic numerical results.